Man and banner - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a bearded man marching beside two individuals who hold a banner with the graphic of a bird with its wings spreadout and a crown during the National March on Washington for Lesbian and Gay Rights. Below the graphic the banner reads, "[San Fran]cisco". Behind these individuals are a large group of marchers.